Foreign Language Learning Boredom in the EFL Classroom and during Independent Language Learning : Examining and Comparing Finnish University Students’ Experiences - Haikonen, Aino (My University, 2023)
Regardless of the universal nature of boredom as an academic emotion, applied linguistic research regarding the emotion has only gained prevalence during the last decade. The present study examines the emotion specifically as Foreign Language Learning Boredom (FLLB) in the context of Finnish bachelor’s degree students studying English as a mandatory part of their degree. The study provides a comparative approach to FLLB experienced in two distinct contexts: the EFL classroom and independent language learning outside of the classroom. In the present study FLLB among 53 bachelor’s degree students was examined in terms of its intensity and common causes, as well as common coping styles and reactions related to the emotion. Intensity of FLLB was investigated statistically through quantitative data that was collected with a questionnaire that was modelled after two preexisting questionnaire tools for both studied contexts respectively. Causes of FLLB and students’ common reactions to the emotion were investigated with qualitative data collection and analysis methods. The study found that students were statistically more likely to experience higher levels of FLLB during independent language learning than they were in the EFL classroom. However, in both studied contexts FLLB scores were considered moderate at most. In both contexts common causes for FLLB were mostly attributed to the achievement setting and language tasks assigned by a teacher. Even during independent language learning which is on the surface less controlled by the teacher’s authority, most FLLB could be attributed to homework tasks or other work directly related to activity in the classroom. On the contrary, students’ coping styles during independent language learning demonstrated more autonomy and freedom than in the EFL classroom. Behavioral coping styles that allow students to change or exit boredom inducing situations as a consequence of their own behavior were commonly used during independent language learning, whereas common coping styles in the EFL classroom included short-term avoidance behavior, such as mobile phone usage, or cognitive reorienting of concentration towards the learning situation.
Keywords: Second Language Acquisition, Achievement Emotions, Foreign Language Learning Boredom